Internet connectivity disruption in Bulgaria (Bulgaria) - Voidly (2026)
CRITICAL severity disruption detected in Bulgaria. Confidence: 65%. Data sourced from IODA.
Network Disruption Incident ID: BG-2026-0025
Keywords: internet disruption; BG; disruption; critical